Dust-Retaining Capacity of Deciduous and Coniferous Trees in Tashkent City, Uzbekistan - E.A. Zeybert; N.G. Akinshina; A.V. Mitusov (Central Asian Journal of Water Research, 2022)
This study aimed to investigate the dust-retaining capacity of tree crowns and analyze the possibility of utilizing this parameter to assess the air dust content in different parts of Tashkent City. The Dust Retention Index is expressed in the dust mass that a unit of green tree mass can hold. The plant material was collected at three sites in Tashkent with different environmental conditions (sunlight, temperature, dust sources) for the following species: catalpa (Catalpa bignonioides Walt.), London plane (Platanus acerifolia), Eldar pine (Pinus eldarica), and cedar red juniper (Juniperus virginiana). The research shows that compared to coniferous species the following deciduous species demonstrate the highest dust retention values: plane (2.4, 1.2, and 13.3 mg/cm2, respectively), catalpa (8 and 3.6 mg/cm2, respectively), pine (0.185, 0.062, and 0.785 mg/cm2, respectively), and juniper (2.2 and 0.4 mg/cm2, respectively). The dust-retaining capacity was calculated based on the total dust emission in Tashkent averaging 24.6±6.9 thou. tons per year (2009-2018). Plane is capable of retaining approx. 0.61%, and pine – approx. 0.16% of the mean annual (2009-2018) aerosol mass (per 100 thou. trees). The calculations allow concluding that in order to compensate (retain) the annual dust emission in Tashkent, approximately 17-19 mln plane trees or 60-62 mln pine trees are necessary.